Exiting Belindia? Lesson from the Recent Decline in Income Inequality in Brazil - Lopez-Calva, Luis F.; Rocha, Sonia (World Bank, Washington, DC, 2013)
After decades of persistent disparities, inequality in Brazil has fallen steadily over the last fifteen years. This robust rate of decline has surpassed the pace of the Latin American region as a whole, and is taking place as inequality rises in several rapid-growth emerging economies in other regions. This document examines the recent trend in income inequality in Brazil, its key policy drivers and some of the challenges ahead. It aims at capturing some of the lessons behind Brazil?s experience to share with other economies in the region and beyond.